Social Work and the Quality of Life Politics - A Critical Assessment - Sandra Landhäußer; Holger Ziegler (Social Work and Society)
The feature of this paper is a critical assessment of the current discourses about quality of life (QoL) and their implications for Social Work. At first it pictures some major historical backgrounds of the discussion on the improvement of life quality as an aim of societal development. In particular three crucial shifts in the politics of QoL - its 'individualisation', its 'informalisation' and its 'culturalisation' - and their implications for Social Work are critically examined theoretically and empirically referring to the results of an own community-study. The paper concludes with an alternative suggestion reflecting the idea of an 'autonomy-based' approach of democratic equality.